BERA PRESIDENTIAL ADDRESS 2013. (April 2014) - Menter, Ian
<x xml:space="preserve">Abstract</x> In his inaugural Presidential Address, given to the BERA Conference 2013 at the University of Sussex, Ian Menter addresses a number of issues concerning educational policy and the contributions that educational research might make to policy development. As BERA approaches its fortieth anniversary, he also sets out some of the responsibilities that the association faces in ensuring the health and quality of education research in Britain.